Length-weight relationship and condition factor of Trachurus trachurus found in the central-east region of the Moroccan Mediterranean - Hanae Nasri; Souad Abdellaoui; Abdelouadoud Omari; Omar Kada; Abdelhafid Chafi; Belkheir Hammouti; Khalid Chaabane (Indonesian Journal of Science and Technology, 2021)
Trachurus trachurus, is a migratory, semi-pelagic species of the Carangidae family living in schools often associated with mackerel. This species is very common in the Mediterranean, and it is found on all Moroccan coasts. This study aims to determine the length-weight relationship and the condition factor (K) of Trachurus trachurus. Thus, 390 specimens were collected between August 2017 and August 2018 in the central-east region of the Moroccan Mediterranean. The parameters of the length-weight relationship were determined and analyzed by length and sex. It appears that this species has better growth in length than in weight, therefore having a negative or lower allometry. It varies according to sex, length, and season. This result shows that Trachurus trachurus in this study is not overweight in its habitat.